A Productivity Prediction Model for Multistage Fractured Horizontal Wells in Shale Gas Reservoirs - Yongchao Xue; Hua Tian; Fengyuan Zhang; Longjun Wang; Qingshuang Jin (Geofluids)
The tiny sizes of pores and throats in shale gas reservoir increase the complexities of the flow mechanisms, which challenge the accuracy of current productivity models during optimization design and prediction for multistage fractured horizontal wells (MFHWs). This paper established a productivity prediction model for MFHWs with cased hole completion and open hole completion. The model couples the gas flow in the matrix, fractures, and wellbore using potential superposition principle and considers multiple mechanisms of gas flows in a shale gas reservoir, such as stress-sensitive effect, wellbore friction, as well as interference between fractures. Based on the developed model, a productivity prediction method for MFHWs in shale gas reservoirs has been established, and sensitivity of the impact factors on productivity was analyzed. The analysis revealed that MFHWs are suitable for shale gas reservoirs with certain thickness. The number of fractures has significant impact on the production of shale gas reservoir. And the fractures at the both sides have higher production rate than the intermediate ones for multistage fractured horizontal wells. The fracture half-length has insignificant effect on the productivity of MFHWs. The production of shale gas reservoir also increases with pressure drop. The wellbore friction has insignificant effect on the production of MFHWs. The findings of this study can provide a basis for scientific evaluation of the production of MFHWs in shale gas reservoirs.